Associations of the Mediterranean diet with cognitive and neuroimaging phenotypes of dementia in healthy older adults. Issue 2 (24th January 2019) - Karstens, Aimee J; Tussing-Humphreys, Lisa; Zhan, Liang; Rajendran, Niranjini; Cohen, Jamie; Dion, Catherine; Zhou, Xiahong Joe; Lamar, Melissa
ABSTRACT: Background: Accumulating evidence suggests that higher Mediterranean diet (MedDiet) adherence is associated with higher global cognitive performance and brain structural integrity as well as decreased risk of Alzheimer disease (AD) and vascular dementia (VaD). Objectives: We directly examined cross-sectional associations between the MedDiet and cognitive and neuroimaging phenotypes associated with AD and VaD (separately) in a cohort of nondemented, nondepressed older adults. Methods: Community-dwelling older adults ( n  = 82; aged ∼68.8 y; 50% female, 50% minority) underwent dietary (Block Food Frequency Questionnaire 2005) and neuropsychological assessments and neuroimaging. MedDiet scores were quantified with the use of published criteria, and participants were divided into High and Low (median split) adherence groups. We focused our neuropsychological investigation on cognitive phenotypes primarily associated with AD [i.e., learning and memory (L&M)] and VaD (i.e., information processing and executive functioning). AD neuroimaging phenotypes consisted of hippocampal and dentate gyrus volumes quantified using T1-weighted images and the FreeSurfer 6.0 segmentation pipeline (http://surfer.nmr.mgh.harvard.edu ). The VaD neuroimaging phenotype consisted of total white matter hyperintensity (WMH) volumes quantified using combined T1-weighted and T2-fluid-attenuated inversion recovery images. Neuroimaging metrics were adjusted for total intracranial volume. Separate multivariable linear regression models controlling for age, sex, education, body mass index, and caloric intake examined the associations between MedDiet groups (High compared with Low) and cognitive and neuroimaging outcomes. Results: When compared with the Low MedDiet group, the High MedDiet group was associated with better L&M performance and larger dentate gyri. MedDiet adherence was not associated with information processing, executive functioning, or WMH. Conclusion: Results highlight the association between increasing MedDiet adherence and specific cognitive and neuroimaging phenotypes that, when altered, are associated with AD.